Problematika Pertanggungjawaban Marketplace dalam Transaksi Elektronik: Disharmoni Regulasi dan Kesenjangan Perlindungan Konsumen Digital - Haromatul Mukarromah Al-Bantani; Nabila Aulia Rahma; Anggi Sri Haryati Simarmata (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal responsibility of marketplace platforms for consumer losses arising from electronic transactions within the framework of Indonesian positive law. Employing a normative juridical method with statutory and conceptual approaches, the analysis focuses on the coherence, adequacy, and adaptability of legal norms governing digital commerce, particularly under consumer protection, trade, and electronic transaction regimes. The findings reveal that existing regulations, including consumer protection law, electronic information and transaction law, and trade law, have not yet fully accommodated the complex, multi-party nature of marketplace ecosystems, resulting in normative gaps and fragmented liability structures. Furthermore, the current liability framework tends to emphasize fault-based principles, which are insufficient in addressing systemic risks and technological asymmetries inherent in digital platforms. This study proposes a reconstructed model of marketplace liability grounded in hybrid principles, integrating strict liability, shared responsibility, and risk-based regulatory mechanisms to ensure more effective consumer protection. The proposed model contributes to the development of a responsive and adaptive legal framework capable of addressing emerging challenges in digital transactions while strengthening legal certainty and fairness in marketplace governance.